Study protocol: A national cross‐sectional study on psychology and behavior investigation of Chinese residents in 2023 - Diyue Liu; Siyuan Fan; Xincheng Huang; Wenjing Gu; Yifan Yin; Ziyi Zhang; Baotong Ma; Ruitong Xia; Yuanwei Lu; Jingwen Liu; Hanjia Xin; Yumeng Cao; et al. (Health Care Science)
Abstract Introduction This study protocol specifies the primary research line and theoretical framework of the 2023 Survey of the Psychology and Behavior of the Chinese Population. It aims to establish a consistent database of Chinese residents' psychological and behavioral surveys through multi‐center and large‐sample cross‐sectional surveys to provide robust data support for developing research in related fields. It will track the public's physical and psychological health more comprehensively and systematically. Methods The study was conducted from June 20, 2023 to August 31, 2023, using stratified and quota sampling methods. A total of 150 cities across 800 communities/villages were surveyed, selected from China (Despite extensive coordination, we have been unable to contact our counterparts in the Taiwan region of China to obtain relevant statistical data). The questionnaires were distributed to the public one‐on‐one and face‐to‐face by trained surveyors. The questionnaires included basic information about the individual, personal health status, basic information about the family, the social environment in which the individual lives, psychological condition scales, behavioral level scales, other scales, and attitudes towards topical social issues. Supervisors conducted quality control during the distribution process and returned questionnaires, logically checked and cleaned for data analysis. Discussion Data collection has been finished, and scientific outputs based on this data will support the development of health promotion strategies in China and globally. In the aftermath of the pandemic, it will guide policymakers and healthcare organizations to improve their existing policies and services to maximize the physical and mental health of the Chinese population. Trial Registration This study was filed in the National Health Security Information Platform (Record No.: MR‐37‐23‐017876) and officially registered in the China Clinical Trials Registry (Registration No.: ChiCTR2300072573).